A new species of Apteranabropsis Gorochov, 1988 from Guangxi, China (Orthoptera: Anostostomatidae: Anabropsinae: Anabropsini) with key to known species - Bian, Xun; Shi, Fu-Ming (Zootaxa, 2015)
This paper describes and illustrates a new species of the genus Apteranabropsis (Anostostomatidae: Anabropsinae) from Guangxi, China, namely Apteranabropsis guangxiensis Bian & Shi sp. nov. A key to all known species of Apteranabropsis is provided.